An atom probe perspective on phase separation and precipitation in duplex stainless steels *This manuscript has been authored by UT-Battelle, LLC under Contract No. DE-AC05-00OR22725 with the US Department of Energy. The United States Government retains and the publisher, by accepting the article for publication, acknowledges that the United States Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. The Department of Energy will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (16th May 2016) - Guo, Wei; Garfinkel, David A; Tucker, Julie D; Haley, Daniel; Young, George A; Poplawsky, Jonathan D
Abstract: Three-dimensional chemical imaging of Fe–Cr alloys showing Fe-rich ( α )/Cr-rich ( α ′) phase separation is reported using atom probe tomography techniques. The extent of phase separation, i.e., amplitude and wavelength, has been quantitatively assessed using the Langer-Bar-on-Miller, proximity histogram, and autocorrelation function methods for two separate Fe–Cr alloys, designated 2101 and 2205. Although the 2101 alloy possesses a larger wavelength and amplitude after annealing at 427 °C for 100–10 000 h, it exhibits a lower hardness than the 2205 alloy. In addition to this phase separation, ultra-fine Ni–Mn–Si–Cu-rich G-phase precipitates form at the α / α ′ interfaces in both alloys. For the 2101 alloy, Cu clusters act to form a nucleus, around which a Ni–Mn–Si shell develops during the precipitation process. For the 2205 alloy, the Ni and Cu atoms enrich simultaneously and no core–shell chemical distribution was found. This segregation phenomenon may arise from the exact Ni/Cu ratio inside the ferrite. After annealing for 10 000 h, the number density of the G-phase within the 2205 alloy was found to be roughly one order of magnitude higher than in the 2101 alloy. The G-phase precipitates have an additional deleterious effect on the thermal embrittlement, as evaluated by the Ashby–Orowan equation, which explains the discrepancy between the hardness and the rate of phase separation with respect to annealing time (Gladman T 1999 Mater. Sci. Tech. Ser. 15 30–36 ).